Weed control methods and micronutrient sprays on weeds and sunflower growth - Dulaimy, J A M A; Sarheed, B R; Abdulkafoor, A H (Plant Science Today, 2025)
An experiment was conducted during the spring seasons of 2022 and 2023 at Agricultural Research Station No. 1, College of Agriculture, University of Anbar, located in Ramadi district, Anbar province, Iraq. The study aimed to evaluate the impact of weed control methods and micronutrient spraying on weed traits and growth characteristics of three sunflower varieties. The experiment followed a randomized completely block design (RCBD) with a split-split plot arrangement and three replications. The main plots included weed control methods (no control, Treflan herbicide treatment and black plastic mulching). At the same time, the sub-plots consisted of three micronutrient spraying treatments (0, first combination and second combination). The sunflower varieties Aqmar, Sakha and Flami included the sub-sub-plots. Results indicated that the mulching treatment significantly reduced weed density and dry weed weight and achieved values ??of (5.96 and 4.33 plant m-1, 11.67 and 8.22 plant m-1, 123.97 and 91.02 g plant-1) for the two seasons, respectively, while enhancing: plant height, leaf area, stem diameter and chlorophyll index. The second micronutrient spray formulation gave the highest averages for most traits. Among the cultivars, Sakha showed the lowest weed density and dry weed weight, Qamar recorded the tallest plants (189.04 and 211.12 cm) for both seasons and Flame showed superior vegetative growth traits. Significant interactions were observed between the study factors, where the mulching combination and Flamy cultivar gave the highest leaf area, stem diameter and chlorophyll content and the three-way interaction of mulching, the second micronutrient formulation and Flamy cultivar achieved the highest chlorophyll content. and the triple interaction of mulching, second micronutrient combination and Flami variety achieving the highest chlorophyll content. In conclusion, black plastic mulching effectively reduced weed density and improved sunflower growth, with the second micronutrient combination and Flame variety showing the best results.